Oxidation Behavior and Interfacial Bonding Properties of NiCrAl Alloys. Issue 21 (1st June 2022) - Li, Zhiqiang; Song, Zhengqi; Li, Tinghua; Li, Shoubo; You, Junheng; Lei, Ping; Zhu, Donglai; Shang, Shanzhai; Zou, Jianpeng
Abstract: The oxidation behavior and oxidation kinetics of NiCrAl alloy were studied by XRD, SEM and the thermogravimetric analysis method. The adhesion strength of the films was characterized by micron scratch tester. The results show that the oxide film has not formed at 600 °C and 700 °C, and an oxide layer of Al2 O3 has formed at 800 °C. Moreover, an oxide layer composed of Cr2 O3 and Al2 O3 has formed at 900 °C. After oxidation at 800 °C for 100 h, partial θ‐Al2 O3 has transformed to steady‐state α‐Al2 O3 and a dense oxide film of Al2 O3 with the thickness of about 620 nm has formed on the surface of the NiCrAl alloy. The oxidation kinetics curve of the alloy obeys the parabolic law and there are two oxidation rate constants in the oxidation process. The oxidation rate constant of 1.58×10 −4  mg 2 ⋅cm −4 ⋅h −1 in the early oxidation period (0∼12 h) and the oxidation rate constant of 1.04×10 −4  mg 2 ⋅cm −4 ⋅h −1 in the late oxidation period (12∼100 h) indicate that the oxidation resistance ability of the alloy increases with the extension of oxidation time. With the increase of the oxidation time, the interface bonding strength between the oxide film and the substrate can be improved and reaches 5.21 N at 800 °C for 100 h. Abstract : The oxidation rate (1.58×10 −4  mg 2 ⋅cm −4 ⋅h −1 ) at the early oxidation period (0∼12 h) is higher than the rate (1.04×10 −4  mg 2 ⋅cm −4 ⋅h −1 ) at the late oxidation period (12∼100 h) indicate that the oxidation resistance of the NiCrAl alloy is improved with the extension of oxidation time. The oxidation mechanism is transformed from the surface reaction control to diffusion control.